MENGUJI KUALITAS PRODUK, HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN ROKOK ELEKTRIK DI SOLORAYA - Dwi Haryono (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2022)
The goal of this research is to find and analyze how the effect of product quality, price, and brand image on decisions in the purchase of e-cigarettes in Soloraya. Since the legality of e-cigarettes in Indonesia and the increasing cigarette tax led to a change in smoking style, further increasing the use of e-cigarettes. The data analysis in this study uses multiple linear regression testing with data processing conducted with statisticalipackage foriSocial Sciencei (SPSS) program tool version 21. Quantitative approaches are the ones used in this research. The sample technique in this study is non-probability sampling with purposive sampling method with a sample size of 100 e-cigarette users in Soloraya. The results of the study stated that the quality of the product individually had an insignificant positive influence on purchasing decisions. Individual price variables have a significant positive influence on purchasing decisions. Individual brand image is positively correlated and insignificant to purchasing decisions. Product quality, price, and brand image, simultaneously contribute to purchasing decisions.Keywords: product quality; price;brand image, and purchasing desicions